The production and stock of college graduates for U.S. States - John V. Winters (W.E. Upjohn Institute for Employment Research, 2015)
The stock of human capital in an area is important for regional economic growth and development. However, highly educated workers are often quite mobile, and there is a concern that public investments in college graduates may not benefit the state if the college graduates leave the state after finishing their education. This paper examines the relationship between the production of college graduates from a state and the stock of college graduates residing in the state using microdata from the decennial census and American Community Survey. The relationship is examined across states and across cohorts within states. The descriptive analysis suggests that the relationship between the production and stock of college graduates has increased over time and is nearly proportional in recent years. Instrumental variables methods are used to estimate causal effects. The preferred instrumental variables results yield an average point estimate for the production-stock relationship of 0.52, but the effect likely decreases with age.
Keywords: I25; J24; R23; 330; college graduates; human capital; migration; higher education policy